Elizabeth Johnson : Questing for God - Schlumpf, Heidi (Book collections on Project MUSE., 2016)
"As a Catholic theologian, writer, teacher, and religious woman, Johnson has searched for 'the living God' and ways to understand God that make sense for our time, perhaps most famously in her groundbreaking book 'She who is.' ... With this first biography of one of the preeminent Carholic theologians of our time, those who have been enriched by Johnson's work will now find themselves inspired by her remarkable life story."--Back cover.